THE EARTH OF ARUNG PALAKKA HIJACKED, THE PEOPLE WERE ALSO TAXED: THE DUTCH’S ECONOMIC POLICY IN BONE (1906-1942) - Amri, Khaerul (Kementerian Pendidikan dan Kebudayaan, 2021)
This study discussed about the economic policy and the application of taxes in Bone during the colonial period. This research used historical research methods involving source search and collection (heuristics), source criticism (data selection), interpretation, and historical presentation or writing historiography. The research result indicated that the political changes proclaimed by the Governor-General of the Dutch East Indies, Joannes Benecditus van Heutzs, in the early 20th century forced the rulers of Bone to surrender full power to the Dutch East Indies government through a military expedition. Bone was then made Gouvernementlanden with various economic policies of taxes. The application of modern colonialism-style taxes in financial administration was able to support the Dutch East Indies continuously improved. Conversely, the economic depression affected the income of the state treasury until the end of power in the colonies.